Analisis Pengaruh Tenaga Kerja, Upah, Dan Jumlah Industri Terhadap Pertumbuhan Ekonomi Di Provinsi Jawa Tengah Tahun 2013-2022 - Putri, Farah Amalia; Woyanti, Nenik (JEMAP, 2025)
In the last ten years, positive fluctuations in economic growth still place Central Java in the last position with the lowest average growth compared to other provinces in Java. The low percentage of growth is not comparable to the growth in the number of workers and wages. In addition, the number of industries has actually decreased. Therefore, this study aims to analyze the effect of labor, wages, and number of industries on economic growth in Central Java Province. This study is a quantitative study with secondary data from the Central Statistics Agency, covering 35 regencies/cities in Central Java in 2013-2022. Based on the results of regression analysis using the fixed effect model, the variables of labor and wages have a positive and significant effect on economic growth. Meanwhile, the variable number of industries has a negative and significant effect. This negative effect might be caused by the increase in the number of industries that is not comparable to the increase in the number of existing workers, so the quantity of industries is unable to absorb the excess labor, resulting in a decrease in regional output. However, wages are the variable with the largest effect compared to other variables